Golf course and orchards along the eastern hills of Santa Clara Valley - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of a golf course and orchards along the foothills of the Santa Clara Valley. The exact location is unknown, but the geography and similar images of golf courses created by J.C. Gordon suggest the location is the San Jose Country Club on Alum Rock Avenue along the eastern foothills. A variety of large and richly styled houses dot the hillside. Most are surrounded by orchards on all sides, and several of the houses appear to be at various stages of construction. In the center of the photograph, several large water tanks are visible on the crests of two hills.